Negative beliefs about back pain are associated with persistent, high levels of low back disability in community-based women. Issue 9 (September 2018) - Alyousef, Bothaina; Cicuttini, Flavia M.; Davis, Susan R.; Bell, Robin; Botlero, Roslin; Urquhart, Donna M.
Abstract: Objectives: Although pessimistic beliefs about back pain are associated with low back pain and disability, our understanding of their role in the natural history of the condition is limited. This study examined the association between beliefs about back pain and the development and progression of low back pain and disability over a 2-year period in community-dwelling women. Methods: A total of 506 women were recruited at baseline to participate in a 2-year cohort study. Beliefs about back pain were measured at baseline using the Back Beliefs Questionnaire, and low back pain and disability were assessed at baseline and 2 years using the Chronic Pain Grade Questionnaire (CPG). Participants were categorized into the following groups based on their CPG scores: no, developing, resolving, and persistent high-intensity pain and disability. Results: Of the 442 (87.4%) women who participated in the 2-year follow up study, 108 (24.4%) and 69 (15.6%) reported high levels of low back pain and disability, respectively. Negative beliefs about low back pain were associated with persistent, high levels of low back disability (M(SE) = 26.1(1.4) vs 31.3(0.31), P  = 0.002), but not persistent, high-intensity pain (M(SE) = 28.9(1.02) vs 31.2(0.33), P  = 0.2), after adjusting for confounders. Women with persistent high-intensity pain and disability had more negative responses to belief statements about the future consequences of the condition compared with those with no, resolving, or developing pain and disability ( P  < 0.001-0.03). Conclusions: This study found that pessimistic beliefs about back pain were associated with persistent high levels of low back disability, suggesting that strategies aimed at improving negative beliefs may reduce the chronicity associated with this condition.